2011
DOI: 10.1021/jp208008m
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Simulations Reveal Structural Disorder in the RAP74-FCP1 Complex

Abstract: We report atomically detailed molecular dynamics simulations characterizing the interaction of the RAP74 winged helix domain with the intrinsically disordered C-terminal of FCP1. The RAP74-FCP1 complex promotes the essential dephosphorylation of RNA polymerase II prior to initiation of transcription. Although disordered in solution, the C-terminal of FCP1 forms an amphipathic helix when bound to RAP74. Our simulations demonstrate that this interaction also reorganizes and stabilizes RAP74. These simulations il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 65 publications
(138 reference statements)
3
24
0
Order By: Relevance
“…The major biophysical methodologies include nuclear magnetic resonance (NMR) spectroscopy [47-54], steady state and time-resolved fluorescence (single molecule and ensemble) spectroscopies [55-58], electron paramagnetic resonance spectroscopy (EPR)[59], small angle X-ray scattering (SAXS)[60-62], and molecular simulations that are used either de novo [63-71] or in synergy with data collected from spectroscopic investigations of IDPs [54, 62, 72-80]. Methodological advances are maturing and evolving to enable comparative assessments of sequence-ensemble relationships for IDPs.…”
Section: Introductionmentioning
confidence: 99%
“…The major biophysical methodologies include nuclear magnetic resonance (NMR) spectroscopy [47-54], steady state and time-resolved fluorescence (single molecule and ensemble) spectroscopies [55-58], electron paramagnetic resonance spectroscopy (EPR)[59], small angle X-ray scattering (SAXS)[60-62], and molecular simulations that are used either de novo [63-71] or in synergy with data collected from spectroscopic investigations of IDPs [54, 62, 72-80]. Methodological advances are maturing and evolving to enable comparative assessments of sequence-ensemble relationships for IDPs.…”
Section: Introductionmentioning
confidence: 99%
“…These elements are more often helical and are thought to provide seeds for binding interfaces (Sivakolundu et al, 2005; Espinoza-Fonseca et al, 2007, 2012; Belle et al, 2008; Espinoza-Fonseca, 2009a; Wright and Dyson, 2009; Kjaergaard et al, 2010; Norholm et al, 2011). Moreover, unbound IDPs can populate collapsed, globular conformations, stabilized by intramolecular interactions of both electrostatic and hydrophobic nature (Marsh et al, 2007; Espinoza-Fonseca, 2009a; Wostenberg et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Although the computational cost increases with an increase in the model size, a decrease in flexibility binding makes conformational sampling easier. Wostenberg et al [62] reported that the C-terminal IDR of FCP1 dynamically fluctuates even in the complex with RAP74. For a wider conformational space including bound–unbound equilibrium applying the enhanced sampling method is promising approach.…”
Section: Coupled-folding and Bindingmentioning
confidence: 99%